Analysis of Physical Environmental Quality and Airborne Bacterial Counts in the Inpatient Wards of Dr. Pirngadi General Hospital, Medan - Diva Aulia Nathasya; Meutia Nanda (Karya Kesehatan Siwalima, 2026)
Air quality in hospital inpatient rooms plays a crucial role in preventing nosocomial infections. Air contaminated with microorganisms can act as a medium for disease transmission when bacterial counts exceed established quality standards. This study aimed to analyze the relationship between environmental physical factors—temperature, humidity, lighting, and sanitation—and airborne bacterial counts in inpatient rooms at Dr. Pirngadi General Hospital, Medan. This research employed an observational analytic design with a cross-sectional approach. The sample consisted of 12 inpatient rooms selected through purposive sampling based on specific criteria. Data were collected through direct measurements of environmental physical conditions and laboratory examination of airborne bacterial counts. The results showed that temperature was significantly and negatively correlated with airborne bacterial counts (r = -0.744; p = 0.006), indicating that lower temperatures tended to be associated with higher bacterial counts. Humidity was significantly and positively correlated (r = 0.748; p = 0.005), suggesting that higher humidity levels increased bacterial counts. Meanwhile, sanitation (r = -0.411; p = 0.184) and lighting (r = -0.552; p = 0.063) did not show a statistically significant relationship with airborne bacterial counts. In conclusion, temperature and humidity are the primary determinants that should be considered in controlling air quality in inpatient rooms. However, sanitation and lighting remain important factors in preventing cross-contamination.